Privacy and security concerns on information disclosure through social media : a case study on IIUM students - Siti Hazar Saharin@Hosrin (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2020)
Information disclosure through social media (SM) is on the rise due to the increased number of new users of social technology. Personal information has been shared uncontrollably, and information disclosure on SM may implicate users' security and safety, which affects them mentally, emotionally, and physically. Cybercrimes like identity theft, cyberbullying, cyber harassment, cyberstalking, and sexual victimisation are among the threats to the SM users, which can cause mental and emotional disturbances. It can be worse when the exposure of personal information on SM makes the user vulnerable and become the target of criminals through cyberstalking, which consequently leads to physical attacks such as kidnapping, raping, and sexual harassment. Based on the numbers of reported cases, youths and students are the most vulnerable target group, and these cases keep on rising in recent years. Due to this current phenomenon, this research aims to investigate the relationship between information disclosure on SM and privacy and security concerns. Sixty-six (66) students of International Islamic University Malaysia (IIUM) participated in this study through questionnaires, and six (6) students participated in a non-reactive online observation. In this research, the researcher compared student's privacy and security concerns from two groups of students who were separated between Science and Technology (S&T) and Non-Science and Technology (Non- S&T) students. The main finding shows that there is a statically significant relationship between information disclosure and privacy and security concerns. The students of IIUM were highly aware of their privacy concerns and awareness. However, on the other hand, their practices towards security concern and awareness are between moderate and low when it comes to the usage of SM. Interestingly, the students from Non-S&T groups obtained slightly higher result on the level of privacy and security concerns compared to the S&T students. Practically indeed, the privacy and security awareness in the use of SM may minimise the exposure to threats towards the students. This study proposes to university to conduct an awareness program to promote and spread awareness on the use of SM among the students. This awareness program will be in line with the direction of CyberSecurity Malaysia program, which is called CyberSAFE. The CyberSAFE program aims at increasing public awareness and knowledge on cyber safety and how to mitigate online threats.